Development of dehydrated candied papaya (Carica papaya L.) - Olympia, Minerva S.D
Dehydrated candied papaya was developed from firm riped papaya using the cabinet dryer. Variables studied were the effect of lime treatment, length of time of syruping, effect of salting on the final product and the determination of the desired appearance of the final product. Results of the objective and subjective tests showed that the best product was that which was not treated with lime prior to syruping, unsalted nd soaked in 60°Bx syrup for 2 days, dried at 120-150°F in a cabinet dryer at 37.2% relative humidity. The finished product has a translucent bright orange color, sticky and chewy texture and slight papaya flavor to characteristic papaya flavor. Rating for general acceptability was "like moderately" to "like very much". The final product has an ascorbic acid content of 28.9 mg/100 g, representing about 78.8% retention of the vitamin. Relative to the drying characteristics of papaya, the drying curve showed that drying operation can be stopped after 2 1/2 hours since no further decrease in moisture content occurred beyond this time.